KEPUASAN PELANGGAN DITINJAU DARI STORE ATMOSPHERE, VARIASI MENU, DAN PELAYANAN PADA COFFEE SHOP KAPAL KOPI KARANGANYAR - Rico Dwi Saputro; Siti Maryam; Sri Hartono (ITB AAS INDONESIA Surakarta, 2021)
This study aims to prove the simultaneous and partial effect of Customer Satisfaction in terms of store atmosphere, menu variations and service on Coffee Shop Kapal Kopi Karanganyar. This research is quantitative descriptive. The population is all Coffee Shop Kapal Kopi Karanganyar buyers. The number of samples used by Sugiyono's guidelines, amounting to 100 respondents, the sample was taken by purposive sampling technique. The data analysis technique used in this study was multiple linear regression analysis. The concluded of this researched is store atmosphere, menu variations and service significantly towards customer satisfaction for Coffee Shop Kapal Kopi Karanganyar. Keywords : Customer Satisfaction, Store Atmosphere, Menu Variations, Service.